FAKTOR DETERMINAN MARJIN BUNGA BERSIH BANK PEMBANGUNAN DAERAH DI INDONESIA: SUATU STUDI DATA PANEL - Raharjo, Pamuji Gesang (Jurnal Keuangan dan Perbankan, 2014)
This paper analyzed the determinants of net interest margins of the regional development banks (BPD) inIndonesia. The empirical specification was focused on the reported net interest rate margin that was assumed tobe a function of two sets variables namely bank internal variable and macro economic factor as the externalvariable. The sample used in this study consisted of eight regional developments banks during the first threemonths of 2008 until the fourth three months of 2012. The results of panel data analysis with fixed effect modelshowed that bank internal factors such as Return on Asset (ROA) and asset growth (LNSIZE) had a contributionto the hight of net interest margin of the regional development banks (BPD) in Indonesia. Furthermore, themarket interest rate as a macroeconomic variable had a positive relationship with the net interest margin of theregional development banks.